Role of Circular RNAs in Preeclampsia - Jia, Ningyi (Dis Markers, 2019)
Circular RNAs (circRNAs) are noncoding RNAs characterized by circular covalently closed structures, which are generated by back-splicing. circRNA is more stable and conserved than linear RNA and exists in various organisms. Preeclampsia (PE), a common hypertensive disorder of pregnancy, has a profound impact on maternal and neonatal mortality and morbidity. Recent studies demonstrated that circRNAs were differentially expressed in PE maternal-fetal interface compared with those in the control and might mediate pathological processes in pregnancy complications. However, the mechanisms of action of circRNAs in PE are still unclear. Here, we provide a comprehensive review on the current state of knowledge on circRNAs associated with PE. We summarize the known expression profiles of circRNAs and discuss their potential application as biomarkers of PE. The possible mechanisms underlying circRNA dysregulation in the etiology of PE are also explored.